Estágio supervisionado em serviço social : em cena a formação presencial em Mato Grosso - Guimarães, Júnior César Gomes (2021)
The present work reflects on the supervised internship in Social Work as an essential component for professional training, not as a mere fulfillment of credits, but recognizing its importance as an element that allows the intern to experience the professional routine as a locus of learning. Its main objective is to analyze the articulation and operationalization of the ABEPSS National Internship Policy in Social Work courses at the UFAS of Cuiabá and Várzea Grande. Therefore, regarding the methodological approach, we chose to use the qualitative approach. We seek subsidies in bibliographic and documentary sources. Initially, to theoretically support the present study, a literature review was carried out through articles and fundamental books for the debate about professional training in Social Work, from the genesis to contemporaneity, and about the supervised internship in Social Work. The second step was the documental research, through Law 8662 of 1993 of regulation of the profession, Code of Ethics of the Social Worker of 1993, Curriculum Guidelines of ABEPSS of 1996, Resolution of CFESS N 533 of 2008, National Policy of Internship of ABEPSS, and the Pedagogical Projects of the Social Service courses of the IES, UFMT, UNIC and UNIVAG, in the State of Mato Grosso. The results found in the Pedagogical Projects show the importance of the ABEPSS Curricular Guidelines to conduct professional training, however, a certain gap was identified between what is contained in the pedagogical projects of the courses and what is recommended in the ABEPSS PNE.